(untitled) (Research, Society and Development, 2022)
The study of Immunology reveals the importance of knowing the role of the Immune System in the body’s defenses and its ability to respond to the action of immune stimulating substances and/or invasion of microorganisms from the environment. This content should be taught in Biology subject, mainly because it is understood that in basic education, conceptual formation and the establishment of relationships between these concepts are essential for the formation of the individual. In that perspective, the objective of the work was to develop a card game, of a ludic, educational and investigative character and to insert it in the context of teaching immunology to middle school students, from a state school in the city of Russas-CE. Diversified methodologies such as the use of games have increased acceptance among students, and these, through the activity, demonstrate a better global understanding of the subjects covered in the discipline. The research was carried out based on the interpretative method in line with the qualitative and quantitative approach. The interpretative analysis of the data revealed a good perception of the students about the proposed theme, therefore, they presented important knowledge for the good understanding of the content in Biology classes. The quantitative results in turn showed that the IMUNOCARDS game helped in understanding the study of Immunology, as well as facilitating the acquisition of information and production of new knowledge. The data also allowed us to realize that the game proved to be a creative, pleasant, attractive, ludic and innovative tool in the teaching of Biology.